CHINAâ€™S INFLUENCE ON AUSTRALIA'S POSITION IN THE SOUTH PACIFIC IN THE SECURITY SECTOR AND DEVELOPING SECTOR - Ramadhani, Suci Nur; Noer, Mohammad (Journal of Social Political Sciences, 2022)
After the economic growth, the government system, and security in the Solomon Islands have started to improve. China is here to increase its influence in the Region. China's presence in the Solomon Islands puts Australia's position at risk. The research entitled "China's Influence on Australia's Position in the South Pacific Region in the Security and Development Sector. (Case Study: the Solomon Islands 2013-2017)â€, has a problem formulation because the influence exerted by China on the Solomon Islands can pose a threat to Australia. This study aimed to determine the influence exerted by China on the Solomon Islands, thus posing a threat to Australia's position in the region, especially in the security and security sector. This research uses the library research method or literature study. Researchers use library research as their research by collecting library data, reading, taking notes, and reprocessing research materials. The theory used to answer the problem is the theory of foreign policy and international security. Based on the results of the analysis, the author can find out that the presence of China in the Solomon Islands has had a major influence on Australia in the region. If China succeeds in exerting influence in the Solomon Islands, it will pose a huge threat to Australia's position on a security.